Improvement of a discharge nozzle damping attachment to suppress fires of class D - Kovalyshyn, Vasyl; Marych, Volodymyr; Novitskyi, Yaroslav; Gusar, Bogdan; Chernetskiy, Volodymyr; Mirus, Olexandr-Zenoviy (Eastern-European Journal of Enterprise Technologies, 2018)
The software package COSMOSFloWorks has been used to study a discharge nozzle damping attachment. A procedure has been proposed to estimate the covering of surface with dimensions of 0.4×0.4 m by a fire-extinguishing powder. It was established that existing discharge nozzle damping attachments are not efficient because at extinguishing light metals they do not effectively reduce the speed of powder supply onto a flammable surface and fan the fire, not being able to cover the burning surface by a fire-extinguishing powder. After putting out the fire the surface that was covered with powder reveals the burnouts. We have modeled the optimal structural parameters for a discharge nozzle damping attachment in order to extinguish fires of class D in the form of a discharge nozzle damping attachment with an elliptical top and a parabolic reflector. It has been proven that a damping attachment with two working surfaces outperforms the previous damping attachment with a single working surface by 30 %. Given this, the fire-extinguishing powder covers the burning surface by a larger layer, preventing the fanning of chips from the surface of a burning metal, thereby shortening the duration of burning and improving the efficiency of a fire-extinguishing powder supply. Experimental study has confirmed that the use of a damping attachment that supplies a fire-extinguishing powder with two working surfaces in order to extinguish fires of class D increases the powder feed to a fire site, reaching above 90 %. The diameter and the shape of the attachment have been determined. The attachment must acquire the form of a diffuser with a diameter of 16 mm. Our development could be used when designing the stationary and portable fire extinguishing systems for light metals and alloys, including incendiary grenades under condition of proper selection of the powder. We have achieved positive results during field tests of the discharge nozzle damping attachment using a make-up fire to burn the shavings of magnesium alloys